Efektivitas Matakuliah Pembelajaran Mikro (Microteaching) terhadap Keterampilan Dasar Mengajar dan Kesiapan Mengajar - Sr.Sipayung R; Sianipar O; Tafonao N; Pardede L; Pasaribu F; Samosir K; Siahaan S; Siregar S; Parhusip W; Tafonao R (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This study aims to evaluate the impact of the effectiveness of microteaching on the teaching skills and teaching preparation of FKIP students. The research hypothesis states that the effectiveness of microteaching will have a positive impact on teaching ability and teaching motivation. The research method used is descriptive and includes data collection using questionnaires and document research. The research population was all FKIP students who took microteaching courses in the even semester of the 2017/2018 academic year, with a sample of 158 students. Research variables include microteaching effectiveness, teaching skills, and teaching motivation, and their validity and reliability were tested. Data were analyzed using the normality test. The results of the analysis show that the effectiveness of microteaching has a positive impact on students' teaching skills and teaching motivation. Recommendations from this research include organizing micro learning materials systematically, providing summaries at the end of learning, and promoting the use of interesting media in the learning process. Through structured training, it is hoped that FKIP students' teaching abilities will increase.